Kepuasan kerja guru-guru aliran pendidikan teknikal dan vokasional di sekolah-sekolah menengah harian daerah Pasir Gudang zon Rinting - Milan, Noriza (2014)
This descriptive study aimed to identify a significant relationship between job satisfaction of teachers of technical and vocational education in secondary schools in the Pasir Gudang Rinting Zone from a present job, salary , opportunities for promotion , supervision and co-workers. A total of 176 teachers of technical and vocational education in secondary schools in the Pasir Gudang Rinting Zone were involved. The instrument for this study is a questionnaire that Job Descriptive Index ( JDI ) which will be used to measure job satisfaction of teachers in technical and vocational secondary schools in the Pasir Gudang Rinting Zone consisting of 72 items based on five variables factor satisfaction of the employment situation at the moment, pay, promotion , supervision, and coworkers. All data were analyzed using SPSS version 20.0 with descriptive and inferential statistical analysis. The T- test and ANOVA results of data analysis for the perception of teachers of technical and vocational education in secondary schools in the Pasir Gudang Rinting Zone on job satisfaction in terms of employment at the present time, pay, promotion, supervision, and coworkers are not affected by gender. Finally, several suggestions were made for action by the parties concerned as well as future research.